Antimicrobial and biochemical characterization of a C-type lectin isolated from pearl spot (Etroplus suratensis). Issue 87 (April 2019) - Rubeena, Abdul Salam; Divya, Mani; Vaseeharan, Baskaralingam; Karthikeyan, Sivashanmugam; Ringø, Einar; Preetham, Elumalai
Abstract: The present study reveals purification and characterization of a C-type lectin from the serum of pearl spot, Etroplus suratensis ( Es-Lec ). The Es-Lec was purified by affinity chromatography with mannose coupled sepharose CL-4B column and it exhibits single band with a molecular weight of 75 kDa in SDS-PAGE. The surface morphology of purified Es-Lec displays the homogeneous nature of protein. A distinct peak with a retention time of 2.958 min was appeared in high performance liquid chromatography (HPLC), X-ray diffraction (XRD) analysis expresses a single peak at 31.8372̊ and MALDI-TOF peaks which shows the purity and crystalline nature of the protein respectively. Functional analysis of purified Es-Lec exhibits yeast agglutination activity against Saccharomyces cerevisiae and has the ability to agglutinate the human erythrocytes, which was observed by light microscopy and haemagglutination inhibition was also done. In addition, purified Es-Lec showed the broad spectrum of antibacterial activity against Gram negative Vibrio parahaemolyticus and Aeromonas hydrophila . Antibiofilm potential of purified Es-Lec against selected Gram-negative bacteria exhibited the disruption of biofilm architecture at the concentration of 50 μg ml −1 and also it exhibited antiviral and anticancer activity. Graphical abstract: Image 1 Highlights: Es-Lec of 75 kDa was purified by mannose-sepharose column chromatography. Its crystalline nature, quality and purity were assessed by XRD, HPLC and MALDI-TOF respectively. Es-Lec exhibited haemagglutination and yeast agglutination activity. They possess antibacterial, antibiofilm and antiviral activity. They exhibited an anti-cancer potential against breast cancer cell lines MDA-MB-231.